EXPLORING HOW DIGITAL LITERACY SUPPORTS STUDENTS' LEXICAL KNOWLEDGE - Rio Rachmat Alam; Nur Aeni; Ryan Rayhana Sofyan (Universitas Negeri Makassar, 2026)
This qualitative study explores how digital literacy supports students' lexical knowledge by investigating their daily interactions with digital platforms. Six digitally literate third-year students at SMA Negeri 3 Makassar participated in semi-structured interviews. Data were analyzed using Braun and Clarke's (2006) thematic analysis with a deductive approach, organized into four pre-determined themes: digital access, digital scaffolding, digital engagement, and self-directed learning. The results reveal that digital literacy supports vocabulary learning in several meaningful ways. Students used a wide variety of digital platforms and tools, deliberately configured their digital environments to maximize English exposure, actively used scaffolding features such as translation tools and AI chatbots to understand new words in context, engaged with English digital content daily through personally meaningful activities, and developed independent vocabulary learning routines without teacher guidance. In conclusion, digital literacy not only facilitates vocabulary acquisition but also nurtures learner autonomy and meaningful engagement with English in authentic digital contexts.